The influence of post-infarct heart failure and high fat diet on the expression of apelin APJ and vasopressin V1a and V1b receptors. (December 2019) - Czarzasta, Katarzyna; Wojno, Olena; Zera, Tymoteusz; Puchalska, Liana; Dobruch, Jakub; Cudnoch-Jedrzejewska, Agnieszka
Abstract: Vasopressin and apelin are reciprocally regulated hormones which are implicated in the pathophysiology of heart failure and the regulation of metabolism; however, little is known about their interactions under pathological conditions. In this study, we determined how post-infarct heart failure (HF) and a high fat diet (HFD) affect expression of the apelin APJ receptor (APJR) and the V1a (V1aR) and V1b (V1bR) vasopressin receptors in the hypothalamus, the heart, and the retroperitoneal adipose tissue. We performed experiments in male 4-week-old Sprague Dawley rats. The animals received either a normal fat diet (NFD) or a HFD for 8 weeks, then they underwent left coronary artery ligation to induce HF or sham surgery (SO), followed by 4 weeks of NFD or HFD. The HF rats showed higher plasma concentration of NT-proBNP and copeptin. The HF reduced the APJR mRNA expression in the hypothalamus. The APJR and V1aR protein levels in the hypothalamus were regulated both by HF and HFD, while the V1bR protein level in the hypothalamus was mainly influenced by HF. APJR mRNA expression in the heart was significantly higher in rats on HFD, and HFD affected the reduction of the APJR protein level in the right ventricle. The regulation of APJR, V1aR and V1bR expression in the heart and the retroperitoneal adipose tissue were affected by both HF and HFD. Our study demonstrates that HF and HFD cause significant changes in the expression of APJR, V1aR and V1bR, which may have an important influence on the cardiovascular system and metabolism. Graphical abstract: Unlabelled Image Highlights: Post-infarct heart failure causes changes in the expression of APJR, V1aR and V1bR. Expression of APJR, V1aR and V1bR are regulated by a high fat diet (HFD). Combination of post-infarct heart failure and a HFD have a different effect.